Echocardiography and cardiac magnetic resonance in children with repaired tetralogy of fallot and their correlations with exercise capacity. (25th November 2020) - Avesani, M; Borrelli, N; Krupickova, S; Sabatino, J; Piccinelli, E; Josen, M; Michielon, G; Fraisse, A; Di Salvo, G
Abstract: Background: Severe pulmonary regurgitation (PR) and progressive right ventricular (RV) dilation and disfunction are common in patients with repaired Tetralogy of Fallot (r-TOF) and should be carefully monitored during the follow up of these patients. In this contest, Echocardiography and Cardiac Magnetic Resonance (CMR) have a complementary diagnostic role. Purpose: To correlate Echo and CMR parameters in children (<18 years) with r-TOF with at least moderate PR assessed by Echocardiography and to analyse which parameter was associated with peak oxygen consumption (Vo2). Methods: Paediatric patients with r- TOF with at least moderate PR at the echo evaluation who underwent a CMR study within six months were included by using hospital databases. All patients underwent standard echo-Doppler study including RV end-diastolic area (RVEDA), end-systolic area (RVESA), fractional area change (FAC) and TAPSE; PR was assessed by Color Doppler, continuous-wave (CW) Doppler and derived parameters such as pressure half time (PHT), PR index, ratio of diastolic and systolic time-velocity integrals (DSTVI) of the main pulmonary artery. By speckle tracking we measured also RV global longitudinal strain (RVGLS) and right atrial strain (RAS). All the patients underwent CMR to assess PR and right ventricular volumes and ejection fraction (EF). Of these, 36 patients underwent cardiopulmonary exercise test (CPET). Results: Fourty-six children (aged 13.7±3.0 years) were included. Echo derived RV areas correlated significantly with CMR RV volumes (r=0.72, p<0.0001). RVEDA >21.9 cm 2 /m 2 had a good sensitivity (83.3%) and specificity (73.5%) to identify a RV end-diastolic volume (RVEDV) ≥150 ml/m 2 . No correlation was found among TAPSE, FAC, RVGLS and RVEF calculated by CMR nor between PHT, PR index and DSTVI and PR-RF. Only A' wave velocity showed a significant but modest correlation with CMR RF (r=0.57, p<0.0001). Flow reversal in pulmonary branches showed a sensitivity of 95.8% and a specificity of 59.1% to identify PR RF ≥35%. RVEF by CMR was preserved in all patients, while TAPSE was reduced in 78.2% and RVGLS in 60.8%. None of the CMR parameters correlated with peak Vo2. At the multivariate analysis RAS was the best independent predictor of peak Vo2 (p<0.0001). Conclusion: In children, flow reversal in pulmonary branches identifies hemodynamically significant PR at CMR. RV area by echocardiogram is a valid first-line parameter to screen RV dilation. Our study suggests that, also for the RV, there is longitudinal systolic dysfunction in presence of preserved RV EF. RAS is the best predictor of peak Vo2 and should be added in the follow up of these patients. Funding Acknowledgement: Type of funding source: None